Performance of the Immediate Post-Concussion Assessment and Cognitive Testing Protocol Validity Indices. (27th October 2017) - Manderino, L M; Gunstad, J
Abstract: Objective: Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT) is a computerized neuropsychological test battery. Athletes provide preseason baseline ImPACT scores to which post-injury scores can be compared to aid concussion diagnosis. However, if baseline scores are not accurately representative of abilities, the utility of post-injury score comparison is diminished. For this reason, ImPACT includes low score thresholds on five validity indices to identify insufficient effort at baseline, though evidence of these indices' performance is limited. The present study examines the classification accuracy and concurrent validity of the existing ImPACT validity indices and three proposed indices (Word Memory Correct Distractors, Design Memory Correct Distractors, Total Symptom Score). Methods: The ImPACT, Word Memory Test (WMT) and Minnesota Multiphasic Personality Inventory-2-Restructured Form (MMPI-2-RF) were administered to 242 undergraduate students. Participants were instructed to either give full effort on testing or to simulate SRC. Results: Sensitivity of the existing ImPACT validity indices was marginally improved with adjusted score thresholds while maintaining acceptable specificity (0.90). Alternative score thresholds and novel validity indices demonstrated adequate specificity while improving sensitivity overall. Positive and negative predictive powers are provided to inform use of protocol validity indices across diverse treatment settings. Conclusions: The existing ImPACT indices' high specificity at the expense of lower sensitivity compared to external validity measures may under-identify poor effort, resulting in premature return-to-play decisions for athletes with concussion. Improvements or additions to the existing indices may raise sensitivity while maintaining acceptable specificity, aiding in the protection of athletes and safe athletic participation.